TEKNIK SANGGAMA DALAM TEKS PAURURAVA MANASIJA SUTRA - I Gede Suwantana (Pascasarjana Universitas Hindu Indonesia, 2018)
The text of Paururava Manasija Sutra in this work is sourced from the Dhundiraja SastrÄ± edition published by Kamakunjalata (Varanasi: Chowkhamba Sanskrit Series Office, 1967), p. 1-27 and commented on by Jayakrsna Diksita. This text is very short, composed of 53 sutras covering techniques of sexual intercourse, timing, enjoyment, age of women invited to intercourse, and techniques for maintaining resilience. The terms used in expressing the techniques, sensations, and patterns contained within them use the spiritual terms commonly used in Yoga and Tantra, for example, the achievement of layered-level pleasures, such as jana loka, tapa loka, satya loka and others. Descriptively this work tries to elaborate in detail the technique of copulation comprehensively by using other kama texts forenrichment, such as Kamasutra, Ananga Rangga and other texts. The Paururava text lays out a good and proper copulation technique that will bring maximum sexual pleasure. Determining the type of opponent in sex is also strongly encouraged by this text so that the results achieved can reach the top.